Aplikasi Pupuk Organik Hayati Cair Untuk Mengurangi Nutrisi AB Mix Terhadap Pertumbuhan Dan Hasil Pakcoy Pada Dua Sistem Hidroponik - Anza, Alfi'; Ali, Fahri; Kartina, Raida; Maulida, Desi; Sesanti, Rizka Novi (Journal of Horticulture Production Technology, 2024)
The use of liquid organic fertilizer with added AB Mix nutrients is an alternative solution to reduce the use of AB Mix nutrients. The aims of the research were to study interaction between the application of liquid organic fertilizer and the hydroponic system on the growth and yield of pak choy and the effect of concentration of liquid organic fertilizer and hydroponic systems on the growth and yield of pak choy. This experiment used Split Plot Design, which consist 2 factors, main plot was concentration of liquid organic fertilizer. Sub plot was hydroponic systems. Data obtained were analyzed with F test, and were continued with LSD at 5 percent when significant. Results showed that there was no interaction between the concentration of liquid organic fertilizer and hydroponic system for all observed parameters. The concentration of 25% liquid organic fertilizer + 75% AB Mix and concentration of 45% liquid organic fertilizer + 55% AB Mix gave better results on the parameters of height, number of leaves and fresh weight of pak choy plants grown in a hydroponic system when compared with a concentration of 65% liquid organic fertilizer + 35 % AB Mix. The NFT hydroponic system is better in the parameters of height and number of leaves of pak choy plants when compared to the DFT hydroponic system.